De novo migraine with aura in the third trimester of pregnancy: a case report and literature review - Paškevičiūtė, Elena; Bužinskienė, Diana; Ryliškienė, Kristina (Acta medica Lituanica, 2021)
Background: Among all headache disorders, migraine has the highest prevalence during gestation. The majority of migraineurs experience improvement during pregnancy, but a few may experience migraine for the first time. This poses a diagnostic challenge in the differential diagnosis between primary and life-threatening secondary headache disorders. Because pregnancy itself is an independent risk factor for secondary headache disorders, it is mandatory to exclude these conditions in order to diagnose migraine. There is a large body of literature about pre-existing migraine course during pregnancy and its link with adverse pregnancy outcomes, but there are no studies examining these aspects among women with new-onset migraine during pregnancy.Case report. A 31-year-old female at 33 weeks of gestation (gravida 2, para 2) was referred to the neurologist eds disturbances, which were followed by pressing severe headache, rated as 8 out of 10 on a numeric rating scale and accompanied by dizziness. The headache lasted for one day, and dizziness continued to the following day. The patient was investigated for a secondary headache disorder, but laboratory and neuroimaging results were unremarkable. A migraine with aura was diagnosed. The patient was advised to keep a consistent sleep schedule, maintain regular low physical activity, eat regularly and take magnesium supplementation. The patient was informed about a safe treatment approach in case of an acute attack. At 40 weeks of gestation the patient delivered female newborn, weighing 3750g, with Apgar scores of 8 and 9 (due to a nuchal cord). The postpartum period was uneventful. During the subsequent 4 years, the patient did not experience any recurrent migraine attacks and had no pregnancies.Conclusion. In order to diagnose a migraine during pregnancy, exclusion of secondary headache disorders is mandatory. Pregnant migraineur should be regularly monitored for adverse birth outcomes. It is essential to educate patients, provide information about the safe treatment of migraine attacks, and explain nonpharmacological prevention and supplementation benefits.
Keywords: Migraine with aura; Pregnancy; Secondary headache disorder; Acute headache; Migraine management